Phase transitions and guest positions state in the nanodisperse TiO2 caused by laser irradiation - Budzuliak, I.M.; Yablon, L.S.; Kotsiubynskyi, V.O.; Ilnitsky, R.V.; Budzuliak, I.I.; Morushko, O.V.; Ilnitsky, N.R.; Sorohtei, T.R. (Physics and Chemistry of Solid State, 2024)
The laser irradiation effect on the guest positions state in TiO2 (anatase) that facilitates lithium ions access to these positions was studied. The method of chemical potential spectroscopy revealed sharp voltage drops and the associated minima in the dependence of the intercalation degree x on the electromotive force ε dx/dε, caused by host-guest system ordering and by coexistence of two phases. From the analysis of the entropy change ΔS in dependence on the introduced lithium amount, it was found that ΔS increase is associated with additional guest positions generation and an increase of the oscillational degrees of freedom quantity in the intercalant. The combined effect of laser irradiation and iron doping on nanodispersed TiO2 provides a stable discharge voltage over a wide range of lithium guest load.